The sustainability of grain production: the impact of agricultural productive services on farmers’ grain profits - Han, Guoying; Cui, Wenchao; Chen, Xiaoxuan; Gao, Qiang (Frontiers in Sustainable Food Systems, 2024)
Increasing farmers' grain profits is crucial for enhancing the sustainability of grain production and ensuring food security. As a widely applied agricultural management means at present, agricultural productive services are of great significance to study whether they can help increase farmers' grain profits. This paper uses the micro-farmer data from the 2020 China Rural Revitalization Survey (CRRS). It employs an endogenous switching regression model and causal mediation analysis methods, which can address endogenous issues, to examine the impact of agricultural productive services on farmers' grain profits and their underlying mechanisms. The results show: (1) Agricultural productive services significantly increase farmers' grain profits and this conclusion is still robust after the robustness test. (2) The mechanism analysis indicates that agricultural productive services increase farmers' grain profits through three pathways: yield enhancement, cost reduction, and efficiency improvement. (3) The heterogeneity analysis shows that agricultural productive services have a greater impact on increasing grain profits for farmers with lower grain profits, smaller operating scales, and lower degrees of farmland fragmentation. Our findings suggest that increasing support for agricultural productive services, fully leveraging the radiative driving role of service providers, and offering farmers various forms of productive services will be key measures to enhance farmers' grain profits, promote sustainable grain production, and ensure food security.